2011
DOI: 10.3904/kjim.2011.26.3.352
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Arterial Embolization as Treatment for a Life-Threatening Retroperitoneal Hemorrhage Complicating Heparin Therapy

Abstract: Spontaneous retroperitoneal hemorrhage is a distinct clinical entity that can present in the absence of specific underlying pathology or trauma and is typically associated with anticoagulation therapy. We report a case of a 74-year-old female patient with a cerebral infarction related to atrial fibrillation who developed a spontaneous lumbar arterial hemorrhage complicating heparin therapy. The diagnosis was suggested by a computed tomography scan and confirmed by angiography. She was treated successfully with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Hypotension and nerve-compression effects characterized by motor or sensory deficits in the groin and thigh may be additional suggestive signs. 7 9 , 11 , 15 , 16 A decline in the Hb level may also aid in a prompt diagnosis in this setting. 17 Although these manifestations should result in a high index of suspicion of the disease, we feel that an early diagnosis as well as awareness of the retroperitoneal bleeding remains a challenge for physicians, despite the accumulation of studies on the nature of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypotension and nerve-compression effects characterized by motor or sensory deficits in the groin and thigh may be additional suggestive signs. 7 9 , 11 , 15 , 16 A decline in the Hb level may also aid in a prompt diagnosis in this setting. 17 Although these manifestations should result in a high index of suspicion of the disease, we feel that an early diagnosis as well as awareness of the retroperitoneal bleeding remains a challenge for physicians, despite the accumulation of studies on the nature of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The mainstay treatment for retroperitoneal bleeding includes withdrawal of the offending agents, correction of the anticoagulation state, volume resuscitation, and other supportive measures, and endovascular techniques and/or open surgical management can be additional therapeutic options. 7 , 11 Subjects with small hematomas and little to no neurological signs may respond well to conservative management, whereas more aggressive interventional approaches should be considered for patients with large hematomas, progressive neurological deficits, and/or hemodynamic instability. 7 , 11 , 16 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quint et al reported the role of femoral vessel catheterization and altered haemostasis in the development of extraperitoneal haematomas (Quint et al 1993). On the basis of these reports, anticoagulant or thrombolytic therapy should be considered a risk factor of post-catheterization retroperitoneal haemorrhage (Cura et al 2000, Park et al 2011, Lodge et al 1973, Luvian et al 2004, Sharp et al 1984, Tomlinson et al 2000, Wasay et al 2001, Witz et al 1999.…”
Section: Risk Factor Of Retroperitoneal Haemorrhagementioning
confidence: 99%
“…Hemorrhage can be either non-traumatic due to underlying pathology or traumatic, including iatrogenic and non-iatrogenic causes, while spontaneous bleeding is a distinct clinical entity, de ned as the bleeding in the absence of any trauma or underlying pathology and is a possible complication of anticoagulant therapy [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%